S104 Targeting the bacterial cytoskeleton of CF pathogens for antimicrobial development–A cautionary tale?. (14th November 2013) - Carnell, SC; Perry, JD; Vollmer, D; Biboy, J; Facchini, M; Bragonzi, A; Vergunst, A; Vollmer, W; Khan, CMA; De Soyza, A
Abstract : Background: Burkholderia cepacia complex (BCC) bacteria are opportunistic pathogens that cause severe lung infections in cystic fibrosis (CF). Treatment of BCC infections is difficult due to the inherent multidrug resistance of BCC. There is a pressing need to find new bacterial targets for antimicrobials. We have previously shown that the novel compound Q22, which is related to A22 and inhibits the bacterial cytoskeletal protein MreB, inhibits growth of BCC bacteria. Aims: We aimed to further analyse the phenotypic effects of Q22 treatment on BCC virulence traits to assess its feasibility as an antimicrobial. Methods: BCC bacteria were grown in the presence of Q22 and a broad phenotypic analysis was performed, including resistance to H2 O2 induced oxidative stress, changes in inflammatory potential of cell surface components and in vivo drug toxicity studies. The influence of Q22 treatment on inflammatory potential was measured by monitoring the cytokine responses of BCC whole cell lysates, purified lipopolysaccharide and purified peptidoglycan extracted from bacterial cultures grown in the presence or absence of Q22 in differentiated THP-1 cells. Compound Q22 was also assessed for toxicity in both zebrafish and mouse infection models. Results: BCC bacteria grown in the presence of Q22 displayed varying levels of resistance to H2 O2 induced oxidative stress with some strains showing increased resistance upon Q22 treatment. An increased response in pro inflammatory activity elected by whole Q22 treated bacterial lysate was observed for cytokines TNFa and IL-1b but this was variable between strains. Further dissection of this response is under investigation. Despite minimal toxicity previously shown in vitro with primary CF cell lines, in vivo studies demonstrated Q22 toxicity in both zebrafish and mouse infection models. Conclusions: In the case of BCC bacteria destabilisation of the bacterial cytoskeleton using compounds such as Q22 can lead to unexpected increases of in vitro virulence-related traits. These changes appear to vary depending on strain and species. Future development of antimicrobials targeting the BCC bacterial cytoskeleton may be hampered if such effects translate into the in vivo environment of CF infection. Work supported by Newcastle-Upon-Tyne Hospitals Special Trustees & Italian CF Research Foundation (FFC).